(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
This study involved the level of pollution with heavy metals and aluminium in the rivers of the Meghriget, Voghchi and Artsvanik. Water samples collected from different sites of the rivers during 2008–2009 were analyzed for Al, Fe, Cu, Mn, Mo, Ni, Pb, Zn, As, Cr, Cd, V, Se. Researches shown that high concentrations of the heavy metals and aluminium in the Voghchi and Meghriget rivers were observed after urban areas. The highest concentration of heavy metals was observed in the Artsvanik river waters which had its impact on the quality of the Voghchi river waters. The maximum permissible concentration (MPC) of aluminium, iron, copper, manganese, molybdenum, zinc, chromium, cadmium, selenium and vanadium was exceeded for culture-domestic water use in the studied river during 2008–2009.